Implementasi Good Governance pada Pelayanan Pemerintah Desa Berdasarkan UUD 1945 - Laelly Wahyu Hidayati; Kharisma Ayu Febriani; Mohamad Djasuli (LP2M Politeknik Jambi, 2022)
Providing the best service is one of the achievements of the village government in order to meet the quality of service. This is a form of state service for officials written in Alenia 4 Preamble to the 1945 Constitution. This research will determine the implementation of good governance in village government services. This study uses literature review research with a descriptive approach. This method is intended to search, evaluate, and synthesize the best available evidence. Performance related to accountability has been good because it is committed to increasing trust. Transaparancy is not good, because it does not match the system created. Openness is good with digital media. The rule of law is not good because there are still violations. So that accountability and openness are good, but the transparency and rule of law still need to be improved for village officials in village government service activitiesProviding the best service is one of the achievements of the village government in order to meet the quality of service. This is a form of state service for officials written in Alenia 4 Preamble to the 1945 Constitution. This research will determine the implementation of good governance in village government services. This study uses literature review research with a descriptive approach. This method is intended to search, evaluate, and synthesize the best available evidence. Performance related to accountability has been good because it is committed to increasing trust. Transaparancy is not good, because it does not match the system created. Openness is good with digital media. The rule of law is not good because there are still violations. So that accountability and openness are good, but the transparency and rule of law still need to be improved for village officials in village government service activities